Performance of Neutral Grounding Resistance and Solid Grounding on 60 MVA Power Transformer - Zuraidah Tharo; Amani Darma Tarigan; Siti Anisah; David Banjarnahor (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2023)
This research will look at the protection system on a 60 MVA power transformer and compare two grounding systems, namely grounding with Neutral Grounding Resistance (NGR) and Grounding Solid (GS). The performance of the two systems will be seen, which is the most effective and efficient. Soil resistance is directly related to water content and temperature; thus, it can be assumed that the resistance of a grounding system will change according to climate change. To obtain a stable grounding resistance, the grounding electrode is installed at the optimal depth to achieve a constant level of water content. The study began by collecting data and then comparing grounding using NGR with GS and measuring the resistance values ​​of NGR and GS on a 60 MVA Power Transformer. The results of this comparison will obtain data on the NGR and GS resistance values ​​on the 60 MVA power transformer, then analyze and compare these values ​​which will provide a conclusion which of the two systems has the best value for grounding.